Six SNPs and a TTG indel in sheep desmoglein 4 gene are in complete linkage disequilibrium - Yue-Hui Ma; Ge, Zhang; Yuan-yue, Zhang; Weijun, Guan; Qian-Jun Zhao; Hui-jing, Zhao; Han Jianlin (2011)
Desmoglein 4 (DSG4) plays an important role in the regulation of growth and differentiation of hair follicles in mammals. In this study, a 755 bp long segment of DSG4 was screened in 544 sheep sampled from nine Chinese indigenous breeds and two Western breeds using PCR-SSCP assay with three different pairs of primers. Two of the three fragments showed polymorphisms with genotypes defined as AA, AB, BB and BC, and DD, DE, and EE, respectively. Interestingly, polymorphisms in these two fragments were in strong linkage disequilibrium. Only three haplotypes were found, of which haplotype AD determined by alleles A and D was the major one in all breeds, while haplotype BE was only found in Chinese breeds that possess divergent frequencies ranging from 0.02 to 0.43; haplotype CD was very rare and present in only one Chinese sheep. Sequences of the three haplotypes showed seven single nucleotide polymorphisms (SNPs) and a TTG insertion/deletion (indel), leading to five amino acid substitutions and a glycine indel. Our study provides valuable genetic markers in evaluating the impact of the DSG4 gene on wool traits in sheep.